El estudio de la cultura en el campo organizativo: orígenes antropológicos y congruencia entre el concepto, los niveles de estudio y la metodología de investigación. - Sánchez-quirós, Isabel (Cuadernos de Estudios Empresariales, 2000)
This paper describes organizational culture concept, which were based on anthropological paradigms. This is the reason of some confusion in organizational field. In this paper, we try to clarify both streams of research, analyzing their similarities and differences. Then, we describe their implications into the definítion of the objectives of the study and their effects on the level of culture that we would study aud the right methodology to test it.
Keywords: Organizational culture; anthropological schools; levels of culture; research metholology